Asimadoline, a kappa-opioid agonist, and satiation in functional dyspepsia - Talley, N. J. (2008)
BACKGROUND: Asimadoline, a kappa-opioid agonist, reduces visceral sensitivity in experimental animal models and may decrease satiation and postprandial fullness in healthy individuals. However, its effect on satiation in functional dyspepsia is unclear, and any symptom benefit has not been explored. AIM: To evaluate the effects of asimadoline on satiation volume and postchallenge symptoms in functional dyspepsia. METHODS: A randomized, double-blind trial evaluated gastric satiation and symptoms before and after 8 weeks of asimadoline 0.5 mg (n = 13) or 1.0 mg (n = 13) or placebo (n = 14) b.d. in patients with functional dyspepsia (Rome II). Gastrointestinal Symptom Rating Scale and Nepean Dyspepsia Index were used to assess symptoms during the 8-week treatment. RESULTS: Over 8 weeks of treatment, asimadoline had no significant effect on maximum-tolerated volume or aggregate symptom score with nutrient drink challenge, and on the mean of the total daily symptom severity score compared to placebo. In a post hoc analysis, asimadoline 0.5 mg significantly increased the maximum-tolerated volume (1217 mL ± 90.2) compared to placebo (807 mL ± 111.8) in patients with higher postprandial fullness scores (P = 0.01). CONCLUSION: Asimadoline overall did not significantly alter maximum-tolerated volume, symptoms postnutrient challenge or symptoms over 8 weeks in functional dyspepsia.